2014
DOI: 10.7150/ijbs.8415
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Fgfr1 in Osteoblasts Enhances Mobilization of EPCs into Peripheral Blood in a Mouse Endotoxemia Model

Abstract: Endothelial progenitor cells (EPCs) contribute to neovascularization and vascular repair, and may exert a beneficial effect on the clinical outcome of sepsis. Osteoblasts act as a component of “niche” in bone marrow, which provides a nest for stem/progenitor cells and are involved in the formation and maintenance of stem/progenitor cells. Fibroblast growth factor receptor 1 (FGFR1) can regulate osteoblast activity and influence bone mass. So we explored the role of FGFR1 in EPC mobilization. Male mice with ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Zhang et al . clearly showed that deletion of FGFR1 in osteoblasts resulted in increased CXCL12 expression in peripheral blood 39 consistent with the microarray results. These data suggest important roles of FGFR1 in regulating osteoblast function, including proliferation and gene expression.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang et al . clearly showed that deletion of FGFR1 in osteoblasts resulted in increased CXCL12 expression in peripheral blood 39 consistent with the microarray results. These data suggest important roles of FGFR1 in regulating osteoblast function, including proliferation and gene expression.…”
Section: Discussionsupporting
confidence: 89%
“…Col2a1-Cre targets chondrocytes and osteoblasts, and inactivation of Fgfr1 resulted in an expanded hypertrophic chondrocyte zone (Jacob et al, 2006;Karolak et al, 2015); however, whether this was a cell-autonomous function of FGFR1 in hypertrophic chondrocytes or a non-cell-autonomous effect of inactivation of Fgfr1 in the osteoblast lineage could not be determined from these experiments. Use of Col1-Cre or OC-Cre to target Fgfr1 in mature osteoblasts resulted in increased bone mass and osteoblast number and no reported effect on bone length (Jacob et al, 2006;Zhang et al, 2014). Use of Dmp1-Cre to target Fgfr1 in osteocytes resulted in decreased osteocyte-specific gene expression but no overt skeletal phenotype (Xiao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Fgfr1 has been targeted with a range of Cre drivers including brachyury (T ), Ap2 (Tfap2a), Prx1 (Prrx1), Col2a1, Col1, osteocalcin (OC; Bglap) and Dmp1 (Jacob et al, 2006;Karolak et al, 2015;Li et al, 2005;Verheyden et al, 2005;Xiao et al, 2014;Yu and Ornitz, 2008;Zhang et al, 2014). With the exception of Col1-Cre, OC-Cre and Dmp1-Cre, which target relatively late stages of development, inactivation of Fgfr1 was in multiple cell lineages that include condensing mesenchyme, chondrocytes and osteoprogenitors.…”
Section: Introductionmentioning
confidence: 99%
“…Both genes, Fgfr1 and Fgfr2, are expressed in the mouse osteoprogenitor lineage. Fgfr1 knockout in mature osteoblasts resulted in increased bone mass and osteoblast number in mice (Jacob et al 2006, Zhang et al 2014. Fgfr1 deletion in osteochondro-progenitors results in increased proliferation and delayed differentiation of osteoblasts (Jacob et al 2006).…”
Section: Endocrine-related Cancermentioning
confidence: 99%